Pengaruh Perlakuan Quenching-Tempering Terhadap Kekuatan Impak Pada Baja Karbon Sedang - Muhammad Yunus (Inovasi Pembangunan : Jurnal Kelitbangan, 2015)
This study discusses about the effect of heat treatment on the metal impact strength medium carbon steel. Heat treatment process applied in this research is the process of quenching and tempering , wherein the heating of the specimen quenching process is done until reaching austenite temperature is 910 ° C which was then held for 30 minutes. After that the specimen was cooled rapidly using oil quenching media. Subsequently , the specimen is heated again ( tempering ) until it reaches the temperature of 300°C , 400°C, 500°C and 600°C. Then at each temperature that tempered is held for 60 minutes. Then the specimen is cooled at room temperature and on specimens that have undergone heat treatment process is conducted impact testing. The average impact strength carbon steel which does not undergo heat treatment process is 0.166 J / mm2. In the steel only experience the quenching process impact strength possessed average is 0,142 J / mm2. In the medium carbon steel which is undergoing a process of tempering 300 ° C is 0.422 J / mm2. At 400°C tempering is 0.525 J / mm2. At 500°C tempering is 0604 J / mm2. At 600°C Tempering is 1.249 J / mm2 with each holding time 60 minutes. From the results of these tests, carbon steel which has the highest impact strength have ductile mechanical character, while carbon steel which has the lowest impact strength have brittle mechanical character.